The Affective Assessment Crisis: Deconstructing the Failure of Internalizing Islamic Ecotheology within the Merdeka Curriculum in PAI - Herawati, Susi; Ramli, Syahrur; Trisoni, Ridwal; Thongin, Arthit; Maimori, Romi; Sesmiarni, Zulfani; Akbar, M Ravi (Scidac Plus, 2026)
This study investigates the